Pectins that Structurally Differ in the Distribution of Methyl‐Esters Attenuate Citrobacter rodentium‐Induced Colitis. Issue 19 (16th August 2021) - Beukema, Martin; Akkerman, Renate; Jermendi, Éva; Koster, Taco; Laskewitz, Anne; Kong, Chunli; Schols, Henk A.; Faas, Marijke M.; de Vos, Paul
Abstract : Introduction: Pectins have anti‐inflammatory properties on intestinal immunity through direct interactions on Toll‐like receptors (TLRs) in the small intestine or via stimulating microbiota‐dependent effects in the large intestine. Both the degree of methyl‐esterification (DM) and the distribution of methyl‐esters (degree of blockiness; DB) of pectins contribute to this influence on immunity, but whether and how the DB impacts immunity through microbiota‐dependent effects in the large intestine is unknown. Therefore, this study tests pectins that structurally differ in DB in a mouse model with Citrobacter rodentium induced colitis and studies the impact on the intestinal microbiota composition and associated attenuation of inflammation. Methods and Results: Both low and high DB pectins induce a more rich and diverse microbiota composition. These pectins also lower the bacterial load of C. rodentium in cecal digesta. Through these effects, both low and high DB pectins attenuate C. rodentium induced colitis resulting in reduced intestinal damage, reduced numbers of Th1‐cells, which are increased in case of C. rodentium induced colitis, and reduced levels of GATA3 + Tregs, which are related to tissue inflammation. Conclusion: Pectins prevent C. rodentium induced colonic inflammation by lowering the C. rodentium load in the caecum independently of the DB. Abstract : Pectins with a low or a high degree of blockiness (DB) both increase microbial diversity and low C. rodentium load in cecal digesta. The pectins protected independent of the DB from C. rodentium ‐induced barrier disruption, intestinal damage and inflammation.